Assessment of Carbon Monoxide (CO) Gas Poisoning in Coal Mining - İbrahim Çınar; Cem Şensöğüt (International Journal of Economic and Environment Geology)
Mine fires are an extremely important problem in underground coal mining in terms of both loss of life, loss of reserves and production stoppages. For this reason, it is necessary to keep the underground under constant control with CO measurements, to constantly monitor it, and to activate a warning system at critical levels. In this study, fires and related CO gas poisoning were evaluated together with the events that occurred, and it was emphasized to what extent they caused mass deaths at a catastrophic level.